Pengembangan Permainan Tradisional Pecah Piring terhadap Perkembangan Sosial Emosional Anak Usia 4-6 Tahun di RA Ikhlasul Amal Medan - Arfin Muhammad; Khadijah Khadijah (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to develop and test the effectiveness of the traditional game "Breaking Plates" as a learning medium to support the social-emotional development of children aged 4–6 years at Raudlatul Athfal Ikhlasul Amal Medan. The background of this study is the low social-emotional abilities of children and the limited use of traditional games in the learning process. The method used was Research and Development with the ADDIE development model. Validation by experts indicated the media was suitable for use. Implementation was carried out on 16 children through pre- and post-tests. Analysis using a Paired T-Test showed significant improvements in empathy, cooperation, and sportsmanship. These results demonstrate that the game "Breaking Plates" is effective as an educational medium to enhance the social-emotional development of early childhood in early childhood education settings.